2008
DOI: 10.1111/j.1365-3083.2008.02070.x
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of Impaired Free Radical Generation and Proinflammatory Cytokines by MCP‐1 in Mycobacterial Pathogenesis

Abstract: Mycobacterium tuberculosis exerts its pathogenic effects mainly via its cell wall glycolipid called Mannosylated Lipoarabinomannan (Man‐LAM), which subverts the cellular inflammatory responses by the suppression of superoxide anion generation in earlier hours, and nitric oxide (NO) generation at later hours of pathogenic invasion. In this paper, we have shown the prophylactic effect of C‐C chemokines, both in vitro and in vivo. Exogenous administration of C‐C chemokines, particularly monocyte chemoattractant p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…Likewise, Man-LAM from Mtb has been shown to suppress oxygen radical and nitric oxide generation. [21]. Other major effects attributed to Man-LAM derived from Mtb include inhibition of macrophage apoptosis and inhibition of phagosome-lysosome fusion [19], [22].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Man-LAM from Mtb has been shown to suppress oxygen radical and nitric oxide generation. [21]. Other major effects attributed to Man-LAM derived from Mtb include inhibition of macrophage apoptosis and inhibition of phagosome-lysosome fusion [19], [22].…”
Section: Discussionmentioning
confidence: 99%
“…The C-C chemokines (two adjacent cysteine residues proximal to the amino terminus, such as MCP-1 and macrophage-inhibitory protein-1␣) and the C-X-C chemokines (such as IL-8, IP-10, and IL-1␤) are putatively involved in the orchestrated recruitment of inflammatory cells conducive to granuloma formation (1,5). MCP-1 expression has correlated with potent nitric oxide generation and the subsequent reduction in the M. tuberculosis loads in murine lungs (19). Similarly, our data provide a correlation between normalized MCP-1 levels and the resolution of the M. tuberculosis infection in patients, as de- In contrast, the interpatient variability of the IP-10 plasma levels in our study suggested that the intrapatient determination of IP-10 expression kinetics may provide a stronger correlation to the anti-M. tuberculosis therapeutic response than the threshold IP-10 level.…”
Section: Discussionmentioning
confidence: 99%
“…46 Importantly, it has been demonstrated that exogenous administration of MCP-1, led to the induction of superoxide anion generation via the restoration of impaired protein kinase C signaling in Man-LAM-treated macrophages, indicating the effectiveness of MCP-1 as a potent immunoprophylactic tool for controlling the mycobacterial establishment within the host. 47 In addition, it has been demonstrated that M. tuberculosisinduced chemokine secretion from macrophages is regulated by different mycobacterial cell wall components. 48 The CC-chemokine subfamily members, particularly CCL5, are potent leukocyte activators and chemoattractants, which have an important role in granuloma formation.…”
Section: Role Of Cc-chemokines In the Activation Of Cells In Responsementioning
confidence: 99%